Digitalization in Financial Education in The Universities (UNWE Yearbook, 2023)
The process of digitalization in the education sphere is the new paradigm and model of high technologies development. The importance of the digital delivery of financial education is growing in parallel with the digitalisation of our societies and economies. Digitalization of education assumes to include two inseparable components – a) classroom learning concepts and b) online learning methods. It is now more important than ever to make sure that the innovative use of digital technologies in the field of financial education effectively contributes to increasing financial resilience and well-being, and that governments design and implement effective digital financial education initiatives.The purpose of this article is to present the impact of digitalization on higher financial education, the challenges facing students and teachers in these process and to analyse the level of digital financial culture. Emphasis is placed on the practical application of the digitalization process in the teaching of financial disciplines in universities.